TINJAUAN KEDUDUKAN PENGGUNA ANGGARAN DAN KUASA PENGGUNA ANGGARAN - Laurensius Arliman S (Arena Hukum, 2015)
AbstractThis research aims to discuss the Status Users Budgets and the Budget User Proxy and Its Implications. This paper uses normative research. Results of this writing, the Regulation number 21 of 2011, or a change to a 2 Regulation No. 13 of 2006 was duly converted again, to make room for the regional head of local government in the Province / District / City, to set a minimum threshold associated with the use of money UP / GU, toward direct payments to third parties related goods and services. Presidential Decree number 54 of 2010, has given space to nominal 100 million, related to spending or procurement for the procurement of goods and services directly. Direct procurement is not to see the properties or provide provisions in terms of spending on goods and services, but it belongs to the category of capital expenditures space. AbstrakPenulisan ini bertujuan membahas Kedudukan Pengguna Anggaran dan Kuasa Pengguna Anggaran dan Implikasinya. Tulisan ini menggunakan penelitian yuridis normatif. Hasil dari tulisan ini, Peraturan nomor 21 tahun 2011, atau perubahan ke 2 Peraturan nomor 13 tahun 2006 sepatutnya diubah lagi, untuk memberikan ruang bagi kepala daerah pemerintah daerah di Provinsi/Kabupaten/Kota, untuk menetapkan batas minimum terkait dengan penggunaan uang UP/GU, terhadap pembayaran langsung kepada pihak ketiga barang dan jasa yang terkait. Keputusan Presiden nomor 54 Tahun 2010, telah memberikan ruang sampai nominal 100 juta, terkait belanja atau pengadaan barang dan jasa atas pengadaan langsung. Pengadaan langsung bukan untuk melihat sifat atau memberikan ketentuan didalam hal belanja barang dan jasa, tetapi hal ini termasuk kategori ruang belanja modal.